Politik dan Kaum Muda dalam Novel Namaku Subardjo Karya Hapsari Hanggarini - Dea Harumi Urbaningrum; Purwati Anggraini (Balai Bahasa Provinsi Riau, 2020)
AbstractThis study aims to describe the problem of young people’s failure in politics found in Hapsari Hanggarini’s novel “Namaku Subardjo”. From the novel, data and object of the research was obtained. The data are in the forms of sentences or dialogues and story units that lead to the correlation between politics and youth. The theoretical foundation is Terry Eagleton's sociology of literature which emphasizes on political ideology. Steps of the research method are: 1) reading Hapsari Hanggarini’s novel “Namaku Subardjo” as a whole, 2) colleting data, 3) classifying the data, 4) analyzing and interpreting the data. The importance of the research is to show that young people must be able to play a role and understand politics in order to advance the Indonesian nation. The result of the research is the role of young people in politics for the sake of advancing the Indonesian nation. Therefore, the relationship between youth and politics is very close, as in the novel “Namaku Subardjo” of which, the main character as a young people began to move to build Indonesian politics. AbstrakPenelitian ini bertujuan untuk mendeskripsikan permasalahan kaum muda yang masih gagal dalam berpolitik yang terkandung dalam novel Namaku Subardjo karya Hapsari Hanggarini. Objek penelitian atau sumber data ialah novel Namaku Subardjo karya Hapsari Hanggarini. Data diperoleh dari kalimat atau dialog, dan satuan cerita yang mengarah pada korelasi politik dan kaum muda. Landasan teori yang diacu ialah sosiologi sastra Terry Eagleton yang menekankan pada ideologi politik. Metode penelitian yang digunakan yaitu: 1) membaca novel Namaku Subardjo karya Hapsari Hanggarini secara keseluruhan, 2) menginventarisasi data, 3) mengklasifikasikan data, 4) menganalisis data dan menginterprestasikan data. Pentingnya penelitian ialah untuk menunjukkan bahwa kaum muda harus mampu berperan dan memahami politik demi memajukan bangsa Indonesia. Hasil penelitian ialah peran kaum muda dalam berpolitik sangat dibutuhkan oleh negara. Oleh karena itu, hubungan antara kaum muda dan politik sangat erat, sama halnya dalam novel Namaku Subardjo, tokoh utama sebagai kaum muda mulai bergerak untuk membangun politik Indonesia.